2016
DOI: 10.1111/bcpt.12657
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Value of Murine Delayed‐type Hypersensitivity Arthritis: A Robust Mouse Model of Rheumatoid Arthritis in C57BL/6 Mice

Abstract: In this MiniReview, we summarize the body of knowledge on the delayed-type hypersensitivity arthritis (DTHA) model, a recently developed arthritis model with 100% incidence, low variation and synchronized onset in C57BL/6 (B6) mice, and compare it to other murine arthritis models. It is desirable to have robust arthritis models in B6 mice, as many transgene strains are bred on this background. However, several of the most widely used mouse model of arthritis cannot be induced in B6 mice without the drawback of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…To highlight the potential of Tan IIA for RA treatment, we first used an AIA mouse model to verify its therapeutic effects. The AIA model has been widely used to clarify the pathogenesis of RA and to explore potential therapeutic targets, including the validation of the therapeutic effects of new drugs (Sardar and Andersson, 2016;Atkinson and Nansen, 2017;Dong et al, 2019;Du et al, 2019). Our experiments showed that AIA mice treated with Tan IIA showed decreased histologic scores and attenuated synovial inflammation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…To highlight the potential of Tan IIA for RA treatment, we first used an AIA mouse model to verify its therapeutic effects. The AIA model has been widely used to clarify the pathogenesis of RA and to explore potential therapeutic targets, including the validation of the therapeutic effects of new drugs (Sardar and Andersson, 2016;Atkinson and Nansen, 2017;Dong et al, 2019;Du et al, 2019). Our experiments showed that AIA mice treated with Tan IIA showed decreased histologic scores and attenuated synovial inflammation.…”
Section: Discussionmentioning
confidence: 67%
“…Eighteen male C57BL/6 mice, about 20 g in body weight each, were divided into three groups randomly: the normal group, AIA model group, and AIA model with Tan IIA treatment group. The protocol for inducing the AIA model was as previously described (Atkinson and Nansen, 2017;Dong et al, 2019;Du et al, 2019;Grötsch et al, 2019), adjusted on some points. The experimental timeline for AIA is shown in Figure 1.…”
Section: Aia Induction and Tan Iia Treatmentsmentioning
confidence: 99%
“…DTH arthritis model. The arthritis model was transferred to female C57BL/6 mice (30,31). As described, the mice were immunized on day 27 with methylated BSA (mBSA, A1009; Sigma, Darmstadt, Germany) in CFA (263810; BD Difco, Franklin Lakes, NJ), followed by an i.v.…”
Section: Arthritis Models and Ab Treatmentmentioning
confidence: 99%
“…Clinical relevance in this aspect reflects the model’s pathophysiological relevance, type of immune response as well as the magnitude and duration of the inflammatory response. As previously described, the DTHA model displays a pathogenesis at least partly resembling the human counterpart [ 26 , 29 ]. The experimental arthritis phenotype is triggered by an unspecific antigen (mBSA, this resembling a neoantigen) and it generates a familiar local inflammation with systemic “spillover”.…”
Section: Resultsmentioning
confidence: 90%